The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/aje.12999
|View full text |Cite
|
Sign up to set email alerts
|

Survey of non‐native small mammals traded in South Africa

Abstract: The sale of live non-native animals has become a social norm and is of global concern.The pet trade industry has become one of the main pathways where non-native small mammals are introduced worldwide. We conducted a questionnaire survey in South African pet shops from September 2018 to September 2019 to gain insights into nonnative small mammalian species trade in South Africa. We also investigated whether the pet shop owners were aware of the South African National Environmental Management: Biodiversity Act … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…In addition, future studies should investigate where pet stores source their bird species to understand the supply chain dynamics. In our parallel study (Shivambu et al, 2021c), we found that breeders, followed by animal rescues and pet shops, were the major suppliers of exotic small mammal pets to pet stores in South Africa. This could be the case for the pet bird supply; however, this warrants investigation.…”
Section: Size Of Trade and Seasonal Variationmentioning
confidence: 87%
“…In addition, future studies should investigate where pet stores source their bird species to understand the supply chain dynamics. In our parallel study (Shivambu et al, 2021c), we found that breeders, followed by animal rescues and pet shops, were the major suppliers of exotic small mammal pets to pet stores in South Africa. This could be the case for the pet bird supply; however, this warrants investigation.…”
Section: Size Of Trade and Seasonal Variationmentioning
confidence: 87%